AN INVESTIGATION INTO LOSS AND GAIN IN THE VIETNAMESE TRANSLATIONAL EQUIVALENTS OF STYLISTIC DEVICES USED IN THE NOVEL SERIES “THE LORD OF THE RINGS” BY J. R. R. TOLKIEN - Nguyễn Thị Minh Tâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Thanks to their special capability to express meaning, stylistic devices play an important role in the success of the novel series The Lord of The Rings. Tolkien‟s writing style, especially, using stylistic devices effectively and skillfully contributes to the success of the novel. The aim of this study is to identify lexical stylistic devices and syntactical stylistic devices in the novel series The Lord of The Rings and investigate loss and gain in terms of lexis, structure, and meaning in their Vietnamese translational equivalents. Based on Galperin's theory of stylistic devices, the study discovers that the lexical stylistic devices employed include simile, repetition, metaphor, and personification, whereas the rhetorical question is the only syntactical stylistic device found. The data of the study collected from this novel were quoted, described and analyzed on the stylistic aspects under qualitative and quantitative approaches. Nevertheless, it cannot be denied that due to the differences between the two languages, loss and gain phenomena are unavoidable especially when stylistic devices in the novel series The Lord of The Rings were translated into Vietnamese. Based on the translation shift theory of Catford, 150 samples of loss and gain were examined to identify occurrences of translation shifts. Therefore, this thesis is carried out to point out and analyze these phenomena with the hope of making a minor contribution to the teaching and learning stylistic devices, especially to English-Vietnamese translation.